2020
DOI: 10.5334/aogh.2735
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Cervical Cancer Screening and Awareness among Women in an Urban Community in South India—A Cross Sectional Study

Abstract: Background: Although the incidence of cervical cancer has declined in developed countries, cervical cancer remains a major problem in those that are developing. Past studies suggest that Indian women, who account for at least one-fourth of the global disease burden, are not routinely screened. Objectives: Among the women living in our low-income urban community in South India, we sought to determine the prevalence of screening and to assess women's knowledge of cervical cancer. Methods: We conducted a communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 12 publications
(18 reference statements)
2
35
0
Order By: Relevance
“…44 An overall prevalence of 0-53.6% screening uptake was reported in a scoping review in sub-Saharan Africa, 45 while 14.3% and 7.1% of Indian urban residents reported a lifetime pelvic examination and cervical screening respectively. 46 Very low number of male participated in this study and findings can therefore not be generalizable. A 2016 study in Jamaica also reported a low number (n=180) as the mean of the screened Jamaicans per calendar year between 1996 and 2005 with a peak of 300 men in the year 1999.…”
Section: Cancermentioning
confidence: 81%
“…44 An overall prevalence of 0-53.6% screening uptake was reported in a scoping review in sub-Saharan Africa, 45 while 14.3% and 7.1% of Indian urban residents reported a lifetime pelvic examination and cervical screening respectively. 46 Very low number of male participated in this study and findings can therefore not be generalizable. A 2016 study in Jamaica also reported a low number (n=180) as the mean of the screened Jamaicans per calendar year between 1996 and 2005 with a peak of 300 men in the year 1999.…”
Section: Cancermentioning
confidence: 81%
“…The articles reviewed showed that age, 9,10,12,18 education 3,[13][14][15][16][17][18][19][20] and per capita income 12,17,18 were significant factors independently associated with adequacy of knowledge, attitude, and practice of Cervical Cancer screening. (Table 1) Among 19 studies reviewed, 18 3,[9][10][11][12][13][15][16][17][18][19][20][21][22][23][24][25][26] reported the knowledge on Cervical Cancer. The overall knowledge on Cervical Cancer among women was 40.22%.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study, in 2020, reported that according to the NFHS (National Family Health Survey) report, 22% of women have undergone a cervical examination in India and the majority of the districts fall in the range of 10–20% [ 33 ] whereas as per 2021 India factsheet, the coverage of Cervical cancer screening coverage, % (age and screening interval, reference) has been reported to be only 3.1% [ 34 ]. Another study conducted in 2020, in south India revealed that only 14.3% had at least one lifetime pelvic exam and 7.1% had undergone cervical cancer screening [ 35 ]. The higher percentage reported here maybe due to the fact that cervical cancer screening may have been perceived by responders as speculum exam or even a pelvic exam of any sort, most likely related to antenatal and pregnancy care.…”
Section: Discussionmentioning
confidence: 99%